Habitar (n)o Bonfim: dinâmicas comunitárias e processo de projecto no Porto oriental - Joana Sofia Gonçalves da Fonseca (2018)
The present thesis aims to analyze different processes of project redevelopmentcarried out in selected 'ilhas' of Bonfim, from the standpointof the current urban housing dynamics taking place in the city of Oporto.At a time when the inequalities in access to housing are becomingmore acute, it is questioned whether each project answers to the needsof the population that is currently being excluded by the existingmarket failure, or serving other interests.In this globalized world where more than half the population lives incities, the access to housing is defined by capital. Real estate investmentsand tourism industries add pressure to the housing clusters bythe consumption and commercialization of the public space, particularlyin places with high cultural and heritage value such as the centerof Oporto. Hence, the supply of housing that meets the needs of localresidents is reduced, thus overriding the interests of visitors to the needsof local residents. Currently, in the continuous search for greaterprofitability, the agents involved in these processes are extending theirrange of action to peripheral areas. Territories such as Bonfim, alwaysassociated with industry and the working class, are now subject tospeculative interests. The 'ilhas', unbelievably, go from a basic housingresource to a typical commodity product of Porto.Given the eminence of population substitution, this thesis arises the architecturalpractice as a mean of constructing solutions to protect thesepopulations. Thus, through the analysis of the networks that supportthe projects, there are sought tools that enhance the contribution of thearchitect in the construction of the access to quality urban housing foreveryone.